How to assess, detect, and manage joint involvement in the era of transformational therapies: Role of point‐of‐care ultrasound. Issue 1 (26th September 2022) - Minno, Matteo Nicola Dario Di; Martinoli, Carlo; Pasta, Gianluigi; la Corte‐Rodriguez, Hortensia De; Samy, Islam; Stephensen, David; Timmer, Merel A.; Winburn, Ian
Abstract: Background: Patients with haemophilia experience recurring hemarthroses, mainly involving knees, elbows and ankles, which lead to haemophilic arthropathy, the major chronic complication of haemophilia. With new approaches to haemophilia treatment leading to fewer joint bleeds and, in some cases, no bleeding events, assessing whether current outcome assessment tools provide adequate sensitivity and specificity for management and care of patients with haemophilia is needed. Methods: An overview of current imaging tools for monitoring joint health, novel osteochondral damage and synovial proliferation biomarkers, and the relationship between assessments for functionality and imaging modalities is provided. Usefulness and sensitivity of point‐of‐care ultrasound (POCUS) to complement other assessments and use of ultrasound to monitor haemophilic arthropathy are also examined. Results: This review provides rationale for haemophilia teams to move beyond traditional outcomes in joint imaging, as well as guidance and evidence on assessment of joint health for potential new treatment modalities, such as gene therapy. The role of POCUS in the existing paradigm for haemophilia care and management along with the use of ultrasound as a complement to other outcome assessment tools are also discussed. Finally, the clinical effects of subclinical bleeding on joint function are described, to motivate screening for synovial proliferation. Conclusion: POCUS can facilitate the early detection of joint damage and can monitor disease progression while providing insights into the efficacy of treatment regimens, and should be considered as an essential assessment tool for managing the care of patients with haemophilia.